Thin wire formulation for 3-D modeling of a ground wire - Wan Ahmad, Wan Fatinhamamah; Thomas, D. W. P.; Christopoulos, C. (2008)
This work is aimed at developing electromagnetic modeling techniques to enable researchers to predict the behaviors of substation grounding system to lightning strikes. Transient responses of a grounding system at a substation of a power plant have been investigated using three 3-D transmissionline models. 3-D TLM algorithm has been used and a better performance of a thin wire model for ground conductors in homogeneous lossy medium was developed for 3-D modeling of a grounding system. A coaxial system has been employed as a simple well behaved structure with parameters which can be found analytically of the transmission-line model in order to develop this thin wire model for the 3-D formulation. It is validated by comparing its characteristic impedance with an airfilled square coaxial transmission line model where the results are in a good agreement.